Dietary L-carnitine improves glycogen and protein accumulation in Nile tilapia via increasing lipid-sourced energy supply: An isotope-based metabolic tracking - Ling-Yu Li; Dong-Liang Lu; Zhe-Yue Jiang; Samwel Mchele Limbu; Fang Qiao; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture Reports, 2020)
L-carnitine is a functional aquafeed additive for enhancing lipid catabolism by elevating mitochondrial fatty acid β-oxidation and modulating energy metabolism to provide a “protein sparing effect”. However, results on the effects of dietary l-carnitine on nutrient metabolism in fish are still conflicting. We explored comprehensively the effects of dietary l-carnitine on energy metabolism in Nile tilapia. We fed Nile tilapia for eight weeks with diets supplemented with l-carnitine or not. We conducted metabolic tracking tests by intraperitoneally injecting individual fish with 14C-labeled palmitic acid (PA), glucose (Glu) and an amino acid mixture (AAs). After the feeding trial, insignificant growth-promoting effect of l-carnitine was obtained in treated fish. However, l-carnitine significantly reduced the lipid content in whole body and muscle accompanied by increasing the free carnitine concentration and fatty acid β-oxidation efficiency. Moreover, l-carnitine elevated concentrations of serum glucose, pyruvate and lactate, and increased glycogen and protein deposition in muscle. These results suggest that ingested glucose and protein prefer to be reserved in carnitine-fed fish with sufficient fatty acids oxidation for energy. Nevertheless, after a 14C-labeled single nutrient injection, carnitine-fed fish showed a higher oxidation rate of [1-14C]-PA, d-[1-14C]-Glu and l-[14C (U)]-AAs. Our study indicates that, the effects of l-carnitine on nutrient metabolism are correlated with the abundance of individual macronutrients such that an inadequate lipid supply would cause dietary l-carnitine supplementation to elevate higher breakdown of glucose and protein for energy generation. The present study provides new insights on the regulation mechanism of l-carnitine on nutrient metabolism in fish.